Simulation of a ship’s roll under different loading conditions - Мирошников, Вадим Владимирович; Нестеренко, Владимир Борисович; Завальнюк, Инна Петровна; Завальнюк, Ольга Петровна (Eastern-European Journal of Enterprise Technologies, 2014)
Despite the modern development of ship’s technical measurement and automation equipment, new ships are equipped with the problem of real-time stability control for long service life merchant ships is relevant today. Simulation of a ship’s roll under different loading conditions, the results of which demonstrate the possibility of creating a device that allows real-time control of the ship stability by determining the metacentric height by the measured roll period was performed in the paper. It was found that the metacentric height is an important indicator of ship stability, which needs continuous monitoring in order to ensure the navigation safety. It was shown that the automatic determination of metacentric height requires a device, simple in design, not containing mechanical parts, excluding the human factor, as well as improving the measurement accuracy and skipper’s decision-making speed. Monitoring of the roll is proposed to carry out by the value of the change in the magnetic field intensity vector with the help of magnetic methods of non-destructive testing using magneto-modulation converters - ferroprobes.